2014
DOI: 10.1177/0194599813519405
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intraoperative Determination of Central Node Metastasis by the Surgeon in Papillary Thyroid Carcinoma

Abstract: Intraoperative determination of central lymph node metastasis by the surgeon is a limited guide for CND in clinically node-negative PTC because of its low sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The concept of therapeutic central neck dissection is well‐established in the treatment of papillary thyroid carcinoma (PTC) . However, the role of prophylactic central neck dissection and the extent of central neck dissection in surgery for PTC remain highly controversial . The support for prophylactic central neck dissection is based on the view that removal of microscopic metastases in the central compartment lymph node prevents recurrence and improves disease‐free and overall survival .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of therapeutic central neck dissection is well‐established in the treatment of papillary thyroid carcinoma (PTC) . However, the role of prophylactic central neck dissection and the extent of central neck dissection in surgery for PTC remain highly controversial . The support for prophylactic central neck dissection is based on the view that removal of microscopic metastases in the central compartment lymph node prevents recurrence and improves disease‐free and overall survival .…”
Section: Introductionmentioning
confidence: 99%
“…1 However, the role of prophylactic central neck dissection and the extent of central neck dissection in surgery for PTC remain highly controversial. 2 The support for prophylactic central neck dissection is based on the view that removal of microscopic metastases in the central compartment lymph node prevents recurrence and improves disease-free and overall survival. 3 Prophylactic central neck dissection is also recommended because of the high frequency of lymph node metastasis, 4 and the surgical difficulty and increased risk of complications when tumors recur in the central compartment.…”
Section: Introductionmentioning
confidence: 99%
“…The most common method of surgical prophylaxis of postoperative HPT is the precision character of surgical manipulations with careful observation of the tacticaltechnical requirements to the surgeon: to identify TG in time, to mobilize precisely and maintain their blood supply [4,7]. At the same time, the small size of PTG and their vessels, the anatomical and embryological peculiarities of localization of these organs, consistency and color similarity with fatty tissue, lymph nodes, often make it impossible to keep them intact structurally and without ischemia.…”
Section: Problem Statement and Analysis Of The Recent Researchmentioning
confidence: 99%
“…Cervical lymph node metastasis (LNM), extra-thyroidal extension (ETE), and distant metastasis are commonly regarded as the independent risk factors of PTC (9)(10)(11). The sensitivity and specificity in detecting cervical LNM by US are superior to those by palpation (12,13), although the value of diagnosis is moderate (36-72%) in clinical node-negative PTC (14). Recently, some authors reported that absence of thyroid capsule and contact with capsule on US were the independent risk factors for cervical LNM or ETE, but the related features were not evaluated in high-risk PTC patients (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%